Effect of increasing the vertical intrusive force to obtain torque control in lingual orthodontics: A three-dimensional finite element method study - Robin N Mathew; Aneesh Katyal; Ashutosh Shetty; U S Krishna Nayak (Wolters Kluwer Medknow Publications, 2016)
Context: Biomechanical differences between lingual and labial orthodontics (LiO and LaO). Aims: To investigate the effects of intrusive forces in lingual technique during retraction treatment mechanics. Settings and Design: Intrusive forces act differently in both techniques because of the different location of force vectors in relation to the center of resistance. Increasing the vertical intrusive force is one of the methods routinely used to prevent the uncontrolled tipping and obtain bodily tooth movement in LaO. However, its effects in lingual technique need to be investigated to derive at an optimal treatment mechanics. Subjects and Methods: Finite element method which has been successfully used to simulate tooth movement and optimize orthodontic mechanics effectively was used in this study. An accurate model of the upper central and lateral incisors with the surrounding structures was developed, and the "ANSYS" version 7.0 software was used for analysis. Results: Intrusive forces as high as 3.6N was required to obtain translation in LiO that too in an undesirable direction. Efforts to obtain torque control by increasing the intrusive force only would not be successful. Conclusion: Forces that produce a translation in LaO tends to produce uncontrolled tipping in lingual technique. To obtain adequate torque control in lingual technique, a combination of the reduction in horizontal retraction forces, increased lingual root torque application, and increase in vertical intrusive forces is desirable.